Ripple formation with intense Gaussian femtosecond laser pulses close to the damage threshold. (1st November 2022) - Teubner, U; Andreev, A; Makin, V; Imgrunt, J
Abstract: The formation of laser-induced periodic surface structures (LIPSS or ripples) is a topic that has been investigated for almost 60 years. More recently with the advent of ultrashort laser pulses this subject has regained interest, in particular, due to interaction regimes that have not been present so far. Consequently a lot of work has been done in that field, especially with comprehensive experimental and theoretical investigations of the scaling of ripple parameters on laser pulse duration, wavelength, applied fluence, shot number and so on. However, there are still a lot of questions. The present work addresses an important issue on that subject. In particular, ripple formation is investigated at high laser intensity, namely at an intensity sufficiently large to generate a femtosecond-laser induced plasma. Thus ripple formation occurs close to damage threshold. Experimental results and theoretical discussion of ripple formation and the interrelation to laser pulse energy deposition, energy transport and sample damage originating from the optical interaction and additional thermal effects, respectively, are discussed. Most important, a reduction of ripple formation threshold with laser intensity and fluence, respectively, has been observed which is associated by a super-linear increase of the ripple area. The scaling of this reduction with laser fluence obtained from theoretical estimates is in good agreement with the experimental data.